2021
DOI: 10.3390/antiox10020295
|View full text |Cite
|
Sign up to set email alerts
|

Protein Lipoxidation: Basic Concepts and Emerging Roles

Abstract: Protein lipoxidation is a non-enzymatic post-translational modification that consists of the covalent addition of reactive lipid species to proteins. This occurs under basal conditions but increases in situations associated with oxidative stress. Protein targets for lipoxidation include metabolic and signalling enzymes, cytoskeletal proteins, and transcription factors, among others. There is strong evidence for the involvement of protein lipoxidation in disease, including atherosclerosis, neurodegeneration, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 213 publications
3
28
0
Order By: Relevance
“…However, it is known, that dual oxidase 1 deficiency can also induce the release of pro-inflammatory cytokines such as IFNγ and TNFα [ 91 ]. The above suggestions are confirmed by studies of other authors, which have shown that the formation of 4-ONE-protein adducts is associated with the inhibition of pyruvate kinase and hsp90 [ 69 ] and high-density lipoproteins dysfunction [ 24 ]. However, since the formation of adducts promotes the inhibition of the activity of these enzymes, the use of CBD may protect keratinocytes from the oxidative stress and inflammation associated with H 2 O 2 action.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…However, it is known, that dual oxidase 1 deficiency can also induce the release of pro-inflammatory cytokines such as IFNγ and TNFα [ 91 ]. The above suggestions are confirmed by studies of other authors, which have shown that the formation of 4-ONE-protein adducts is associated with the inhibition of pyruvate kinase and hsp90 [ 69 ] and high-density lipoproteins dysfunction [ 24 ]. However, since the formation of adducts promotes the inhibition of the activity of these enzymes, the use of CBD may protect keratinocytes from the oxidative stress and inflammation associated with H 2 O 2 action.…”
Section: Discussionsupporting
confidence: 70%
“…This may significantly improve the efficiency of their proteolytic degradation and, consequently, prevent pathological accumulation in keratinocytes. Despite the lack of direct data on the effect of 60 kDa chaperonin on MDA-protein adducts formation, it is known that 4-HNE/4-ONE modifications can lead to loss of activity of the chaperone proteins Hsp70 and Hsp90 [ 69 ]. Thus, a reduction in MDA-protein adduct formation may suggest a protective effect of CBD against the 60 kDa chaperonin.…”
Section: Discussionmentioning
confidence: 99%
“…In SLE, oxidative stress is involved in the formation of advanced glycation end products (AGEs) and advanced lipoperoxidation end products (ALEs), compounds with proinflammatory characteristics. AGEs and ALEs synthesis is realized through condensation reactions between electrophile and nucleophile reactants [ 17 , 21 , 22 , 23 , 24 , 25 ]. AGEs and ALEs are immunogen and they determine antibodies synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that liver pathologies such as non-alcoholic fatty liver disease (NAFLD) and non-alcoholic hepatitis (NASH), contribute to lipid disorders commonly terms as dyslipidemia [ 4 ]. Phospholipids containing polyunsaturated fatty acids (PUFAs) are particularly susceptible to the action of reactive oxygen species (ROS), which promote peroxidation based on the classic chain reaction mechanism, resulting in the generation of low-molecular-weight, reactive α,β-unsaturated aldehydes and/or cyclic derivatives such as isoprostanes or neuroprostanes depending on the type of oxidation of the PUFAs underwent [ 5 , 6 ]. Phospholipid oxidation also takes place under the influence of lipolytic enzymes such as: phospholipases, lipoxygenases and cyclooxygenases, which activities are enhanced during oxidative conditions.…”
Section: Introductionmentioning
confidence: 99%